Pengaruh Customer Engagement, Perceived Quality, dan Perceived Value Terhadap Repurchase Intention pada Produk Mcdonald's - Mohamad Rafli Azhar; Sophiyanto Wuryan (MES Bogor, 2024)
The current condition of society is that their lifestyles are becoming increasingly sophisticated, accompanied by their increasing consumption tastes, creating a situation where choosing products becomes more thorough and thorough. The main aim of this research is to determine the influence of Customer Engagement, Perceived Quality, and Perceived Value on Repurchase Intention. The sampling technique used in this research was purposive sampling with a nonprobability sampling method. The number of respondents used in this research was 90 respondents with the criteria being men and women aged minimum 18 years, and had purchased McDonald's products at least 2 times within a period of 1 month. The analytical method used is multiple linear regression. The results of this research prove that customer engagement, perceived quality and perceived value felt by users can increase repurchase intention for McDonald's products so that they can attract consumers minimum 18 years to repurchase intention for McDonald's products. Customer engagement, perceived quality and perceived value can increase repurchase intention for McDonald's products. This of course benefits businesses, especially fast food businesses and creates company success in the long term.